IDENTIFIKASI POTENSI CALON INDUK IKAN NILA (OREOCHROMIS NILOTICUS) DI BENDUNGAN BATUJAI DAN PENGGA KABUPATEN LOMBOK TENGAH: Identification Potency Of Parent Candidate Nila Fish (Oreochromis Niloticus) in The Batujai And Pengga Dam The Central Lombok Districts - Alfian Husnul Ridho; Evron Asrial; Lalu Achmad Tan Tilar WSK.; Al Furkan (Yayasan Al-Amin Qalbu, 2023)
Tilapia (Oreochromis niloticus) is one of the most widely cultivated freshwater fish species in Indonesia. This study aims to determine the biological conditions of tilapia, the level of gonad maturity (TKG) and tilapia fecundity, and the water conditions of the Batujai and Pengga Dam. Examples of fish caught in October-November 2018 in the Batujai and Pengga Dam were 17 and 16 individuals / dams. Identification for collecting morphometric data (11 characters) and gonads was carried out at the 45 Laboratory of the University of Mataram. Morphomteric measurements were quantitatively processed to describe the morphology of tilapia. Relationship pattern of tilapia morphometric characters in Batujai Dam: C = -a + b P, LWR pattern: ln B = -a + b ln P, and the pattern of growth is hyper allometric (b = 3.95). While the pattern of relation of tilapia morphometric characters in the Pengga Dam: C = -a + b P, LWR pattern: ln B = -a + b ln P, and the pattern of growth is hypo allometric (b = 2.75). The condition factor (K) of tilapia from the two dams yields an average value of K> 1 which is (1,627 and 1,926) which means that the fish body shape is fleshy and its physical condition is ready to reproduce